Orbital metastasis of myxofibrosarcoma - Marissa K. Shoji; Shanlee M. Stevens; Oded Ohana; Kevin D. Clauss; Vincent D. Tang; Rayan Abou Khzam; Andrew E. Rosenberg; Sander R. Dubovy; Wendy W. Lee (Taiwan Journal of Ophthalmology, 2023)
Myxofibrosarcoma (MFS), a common sarcoma in adults, typically affects the extremities. Primary orbital involvement is uncommon, and orbital metastasis is exceedingly rare. We describe a case of orbital MFS due to metastasis and provide an updated literature review. A 56-year-old woman presented with 2 months of progressive right eye proptosis. Relevant history included left palmar MFS excised 2 years prior. Examination demonstrated proptosis and restriction in abduction of her right eye without optic nerve compromise. Imaging revealed a well-circumscribed right orbital mass. Initial biopsy showed glandular tissue with chronic inflammation without an evidence of malignancy. She subsequently developed worsening proptosis, complete ophthalmoplegia, and a new afferent pupillary defect. Repeat orbital excisional biopsy with deeper dissection demonstrated high-grade MFS consistent with metastasis. She underwent chemoradiation with resolution of her lesion. Literature review identified 12 previously reported cases of MFS, only two of which involved metastasis to the orbit and were associated with worse prognosis. This report highlights a rare case of orbital metastasis of MFS with high-grade features confirmed on histopathology and provides an updated literature review. Prompt diagnosis and complete removal of MFS located both systemically and in the orbit are essential due to the metastatic potential.